The hidden interplay between sex and COVID-19 mortality: the role of cardiovascular calcification - Alberto Cereda; Marco Toselli; Anna Palmisano; Davide Vignale; Riccardo Leone; Valeria Nicoletti; Chiara Gnasso; Antonio Mangieri; Arif Khokhar; Gianluca Campo; Alessandra Scoccia; Matteo Bertini; et al. (GeroScience, 2021)
Recent clinical and demographical studies on COVID-19 patients have demonstrated that men experience worse outcomes than women. However, in most cases, the data were not stratified according to gender, limiting the understanding of the real impact of gender on outcomes. This study aimed to evaluate the disaggregated in-hospital outcomes and explore the possible interactions between gender and cardiovascular calcifications. Data was derived from the sCORE-COVID-19 registry, an Italian multicentre registry that enrolled COVID-19 patients who had undergone a chest computer tomography scan on admission. A total of 1683 hospitalized patients (mean age 67±14 years) were included. Men had a higher prevalence of cardiovascular comorbidities, a higher pneumonia extension, more coronary calcifications (63% vs.50.9%, p<0.001), and a higher coronary calcium score (391±847 vs. 171±479 mm 3 , p <0.001). Men experienced a significantly higher mortality rate (24.4% vs. 17%, p =0.001), but the death event tended to occur earlier in women (15±7 vs. 8±7 days, p = 0.07). Non-survivors had a higher coronary, thoracic aorta, and aortic valve calcium score. Female sex, a known independent predictor of a favorable outcome in SARS-CoV2 infection, was not protective in women with a coronary calcification volume greater than 100 mm 3 . There were significant differences in cardiovascular comorbidities and vascular calcifications between men and women with SARS-CoV2 pneumonia. The differences in outcomes can be at least partially explained by the different cardiovascular profiles. However, women with poor outcomes had the same coronary calcific burden as men. The presumed favorable female sex bias in COVID-19 must therefore be reviewed in the context of comorbidities, especially cardiovascular ones.